2016
DOI: 10.1177/1049909116673300
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care Patterns at a Community Hospital: The Rest of the Story

Abstract: We undertook a retrospective review of a subset of expired patients at our community hospital to evaluate end-of-life care patterns and the use of advanced care planning tools among patients who died in the hospital. These 162 expired patients fell into 1 of the 3 diagnosis-related groups of cardiac, respiratory, or infectious disease. Seventy-nine percent of patients arrived to the hospital with no requested limitations in the extent of resuscitative efforts, even though 98% of all patients had major or extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…In these studies, multiple barriers have been identified, including lack of clinician engagement, alert fatigue, restricted or biased prediction models, and limited practice capacity for serious illness conversations . Our study offers an example of how these challenges can be partially attenuated while also demonstrating that mortality risk-based predictions can be applied in a community setting, which has been previously highlighted as a need . Clinician fatigue was mitigated by a combination of manual medical record review to ensure the appropriate patient selection and targeted messages in lieu of pop-up or click-through alerts.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In these studies, multiple barriers have been identified, including lack of clinician engagement, alert fatigue, restricted or biased prediction models, and limited practice capacity for serious illness conversations . Our study offers an example of how these challenges can be partially attenuated while also demonstrating that mortality risk-based predictions can be applied in a community setting, which has been previously highlighted as a need . Clinician fatigue was mitigated by a combination of manual medical record review to ensure the appropriate patient selection and targeted messages in lieu of pop-up or click-through alerts.…”
Section: Discussionmentioning
confidence: 93%
“…[40][41][42] Our study offers an example of how these challenges can be partially attenuated while also demonstrating that mortality risk-based predictions can be applied in a community setting, which has been previously highlighted as a need. 43 Clinician fatigue was mitigated by a combination of manual medical record review to ensure the appropriate patient selection and targeted messages in lieu of pop-up or click-through alerts. Our mortality model was shown to apply broadly to all inpatients, even in the modern COVID-19 era, and our palliative care team was closely involved in our implementation to ensure sufficient resources were readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care screening has been proposed to ameliorate this issue. 32 Zalenski et al 33 suggest that hospitals can decrease ICU LOS and reduce costs when all patients in the ICU undergo palliative care screening with subsequent consultation. Preintervention analysis in our study revealed that many of our patients who required EOL discussions came from the liver transplant surgical service; thus, communication between this service and the SICU team helped identify specific patients who warranted supportive care consultations.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests some degree of inconsistency between a patient’s status and how the prognosis is perceived by clinicians, family members, or both. Palliative care screening has been proposed to ameliorate this issue . Zalenski et al suggest that hospitals can decrease ICU LOS and reduce costs when all patients in the ICU undergo palliative care screening with subsequent consultation.…”
Section: Discussionmentioning
confidence: 99%
“…The American Society of Clinical Oncology, National Comprehensive Cancer Network, European Society of Medical Oncology, and other national and international guidelines recommend timely referral to palliative care to optimize patient-centered and goal-concordant care as early as at the time of diagnosis through survivorship or the end-of-life [ 12 , 13 , 14 ]. Despite these recommendations, referrals to palliative care are commonly deferred until patients are profoundly symptomatic when treatment options become limited at the end of life or not considered at all [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%